Circulating irisin levels in patients with MAFLD: an updated systematic review and meta-analysis - Shen, Chenglu; Wu, Kaihan; Ke, Yani; Zhang, Qin; Chen, Shuaihang; Li, Qicong; Ruan, Yuting; Yang, Xudan; Liu, Shan; Hu, Jie (Frontiers in Endocrinology, 2024)
Current research suggests that irisin is closely linked to the pathogenesis and progression of metabolic dysfunction-associated fatty liver disease (MAFLD). This systematic review and meta-analysis updates our previous meta-analysis and further explores the relevance between circulating irisin levels and MAFLD.Nine databases (PubMed, EMBASE, Cochrane Library, CNKI, Wanfang, Weipu, CBM, Clinicaltrials.gov and gray literature) were retrieved as of 1 st August, 2024. The standardized mean difference (SMD) and 95% confidence interval (CI) represent pooled effect size. We used the Newcastle-Ottawa Scale to evaluate the quality of articles and the certainty of evidence assessed by GRADE system. All statistical analyses were performed using RevManRESULTS: Fifteen case-control studies were included. Circulating irisin levels in the MAFLD group were markedly lower than those in the healthy group (SMD=-1.04 [-1.93, -0.14]).Subgroup analyses by race, age, severity and T2DM revealed that circulating irisin levels were lower in the MAFLD group compared to those in the healthy controls in the Asian population (SMD=-1.38 [-2.44, -0.31], P<0.05) and in those above 50 years old (SMD=-2.23 [-3.64, -0.81], P<0.05) and higher in the mild MAFLD groups than those in moderate to severe MAFLD groups (SMD = 11.68 [9.05, 14.31], P<0.05). And the circulating irisin levels in MAFLD patients with T2DM were significantly lower than those in healthy group (SMD = -2.90 [-4.49, -1.30]). ELISA kits from different companies also presented different relationships.CONCLUSIONS: There were significantly lower circulating irisin levels in the MAFLD group than in the healthy control group. Although these results differed from our previous results, there is no denying that circulating irisin levels are closely associated with the advancement of MAFLD.